Resources and time pressure as day-level antecedents of work engagement - Kühnel, J. (Institutional Knowledge at Singapore Management University, 2012)
This diary study adds to research on the Job Demands-Resources model. We test main propositions of this model on the level of daily processes, namely, additive and interaction effects of day-specific job demands and day-specific job and personal resources on day-specific work engagement. One hundred and fourteen employees completed electronic questionnaires three times a day over the course of one working week. Hierarchical linear models indicated that day-specific resources (psychological climate, job control, and being recovered in the morning) promoted work engagement. As predicted, day-specific job control qualified the relationship between day-specific time pressure and work engagement: on days with higher job control, time pressure was beneficial for work engagement. On days with lower job control, time pressure was detrimental for work engagement. We discuss our findings and contextualize them in the current literature on dynamic and emergent job characteristics.